English Diphthong Pronunciation Problems Encountered by the Fourth Semester Students of English Language Education Program at Qomaruddin University - alimin, alimin (Universitas PGRI Adi Buana Surabaya, 2022)
Pronunciation is the production of speech sounds for communication. Many Indonesian students found difficulties in pronouncing English words correctly. This study aims at investigating the students’ pronunciation of English diphthong of the fourth semester students of English Language Education Program at Qomaruddin University. A descriptive qualitative design is applied in this study. 31 respondents are the main source in collecting the data. To collect the data, two instruments used. They are test and interview. The respondents are asked to read a certain text and read some vocabulary while the writer is examining them once. As the result, the writer found 512 errors in reading text. The most source of errors was in pronouncing English diphthong /əʊ/ 207 errors or 40,43%. There were 221 errors in reading vocabularies. The most source of errors was in pronouncing English diphthong /eɪ/90 errors or 40,72%. This study also found the substitution, insertion and omission as the error types of pronunciation. In reading text was found 329 errors or 64,76% of substitution, and 160 errors or 31.50% of omission. Meanwhile, in reading vocabularies there were 111 errors or 51,39% of substitution and 104 errors or 48,15% of omission. However, the result of the interview had found difficulties in pronouncing English diphthong such as difficulties to memorize diphthong sounds and influenced of their mother tongue. Meanwhile, as the students, the most important thing is to know about knowledge and practice. It means that they have to know the phonetic transcription and practice more and more to have good pronunciation.